Competitive Advantage Strategies of the Retail Business of Industrial-grade IT Equipment in Thailand - Phanich, Therdpoom; Chemasangkanan, Suwat; Tanyong, Pongsan (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This research aimed to: (1) examine the fit of a causal factor model influencing competitive advantage and business performance with empirical data; (2) investigate causal factors influencing competitive advantage and business performance; and (3) identify the most appropriate competitive advantage strategies. A mixed-methods research design was employed, with the research context being the retail business of industrial-grade IT equipment in Thailand. For the quantitative phase, the sample consisted of 440 small enterprise operators selected through proportional quota sampling. Data were collected using questionnaires and analyzed using descriptive statistics and structural equation modeling. For the qualitative phase, 15 key informants were selected through purposive sampling, with data collected via in-depth interviews and analyzed using inductive content analysis. The results indicated that the model demonstrated a good fit with the empirical data. The knowledge-based perspective is the strongest influence on competitive advantage, followed by dynamic capabilities and technology and innovation management. Competitive advantage has the strongest influence on business performance, functioning as a full mediator for dynamic capabilities and technology and innovation management, whereas the knowledge-based perspective demonstrates both direct and indirect effects. Qualitative findings confirm that knowledge constitutes the most critical strategic resource, that technology implementation is more important than technology exploration, and that a focus strategy combined with differentiation is most appropriate for this business context. This study contributes to the academic literature by integrating three theoretical perspectives within a single framework and provides practical guidance for entrepreneurs to formulate competitive strategies based on specialized knowledge.